The influence of organizational climate dimensions on ergonomics citizenship behaviour: A conceptual framework / Che Norazri Che Din and Nik Ramli Nik Abdul Rashid - Che Din, Che Norazri; Nik Abdul Rashid, Nik Ramli (Universiti Teknologi MARA, Kedah, 2017)
Musculoskeletal disorder (MSD) is one of the occupational diseases which is caused by exposure of workers to ergonomic risk factors. Statistics from the Malaysian Department of Occupational Safety and Health showed a staggering 160% increase in work-related MSD from 2005 to 2009. In an effort to address this issue, many studies had been conducted to improve workplace ergonomic condition and behaviour. While most MSD-studies have been focusing on the work method and body posture, this article explores an alternative intra-group dynamic construct of employee proactive behaviour towards ergonomics or Ergonomic Citizenship Behaviour (ECB) which is believed could positively influence workplace ergonomics issues. The concept of ECB is adopted from Organizational Citizenship Behaviour (OCB) which had been linked with various positive outcomes. Specific organizational climate factors (employee autonomy, participative decision making, and supervisory support) are also discussed as the predictor variables of the theoretical framework. The Social Exchange Theory is applied to strengthen the empirical justifications and explain the theoretical framework that draws attention to the mutually contingent and rewarding transactional process between both the workers and the organization.